Struktur Kepemilikan dan Nilai Perusahaan: Corporate Social Responsibility Disclosure sebagai Variabel Mediasi - Robert Jao; Paulus Tangke; Anthony Holly; Natasya Gabriella Wijaya; Syafrimansyah Syafrimansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2026)
This research aims to investigate the influence of ownership structure on firm value through the lens of corporate social responsibility disclosure. The grand theory used is stakeholder theory. This research collects secondary data, including financial reports and sustainability reports, from manufacturing companies listed on the Indonesia Stock Exchange during the 2021-2024 period. The results show that institutional ownership has a positive and significant effect on corporate social responsibility disclosure (CSRD), while public ownership has no significant effect. Conversely, institutional ownership and public ownership have a direct positive effect on firm value, while CSRD has no significant effect. Furthermore, CSRD was found not to mediate the relationship between ownership structure and firm value. This indicates that the market responds more directly to ownership structure when assessing companies than to the social disclosure information presented